براہوئی ادب ٹی فارسی آن مٹ و بدل: عبد الخالق ابابکی نا کاریم : Abdul Khaliq Ababakki; Persian Translator in Brahui Literature - Malik, Muhammad Ibrahim; Muhammad Bilal (Al-Burz, 2021)
There have been effects of Persian language on Brahui language and literature like the other languages of subcontinent. Due to being state language, all kinds of orders, religious decisions and documents were written in Persian. In orders to explain these things to Brahuis, there has been need of translation from the very first day. The thoughts of a language can be transferred into the other language through translation which causes the language develop. Therefore, we can find that the old and available books of Brahui to have been translated from Persian like Tofat-ul-ajaib etc. This series continued till establishment of Pakistan, later it grew quiet lesser. However, scholars, now-a-days, are also translating curriculum books of madressas into Brahui, one of these translators is also Maulvi Abdul Khalique Ababaki who has done poetic and prosed / versified Brahui translation of about a dozens of Persian books, out of which Bagh-e-Brahui, Panth Nama, Ramuzath-e-Ishq, Manajath-e-Allama Roomi and Aadenk are very famous. The above mentioned scholar had thorough mastery over all the rules and regulations of translating. Moreover, he himself was an experienced teacher, poet and translator of Brahui and Persian language. That's why his translation, among Persian translation, in Brahui literature, holds immense importance. Some of his translation is still unprinted which includes Waslet Nama, Wahdat Nama and Phul-e-Brahui.